A Sorting-Based Approximation of the Sum-Product Algorithm 10.14209/jcis.2003.6 - Hu, Xiao-Yu; Mittelholzer, Thomas (Journal of Communication and Information Systems, 2015)
A complexity-and delay-efficient simplification of the sum-product algorithm (SPA) for decoding lowdensity parity-check (LDPC) codes is presented. The key feature of the new algorithm consists of a modification of the complexity-intensive and delay-causing update equations at the check nodes of the factor graph of the LDPC code. The modified update equations at a check node are based on ordering the reliability values of the incoming messages and on using a balanced tree topology to achieve optimum parallel processing. Furthermore, the complexity of the new algorithm can be adjusted: the least complex version of the algorithm corresponds to the so-called min-sum approximation, and the most complex version gives the full SPA.